Interspecies Experience of Illness. Anthropological Approach to Several Texts by Janina Degutytė - Šmitienė, Giedrė (Tautosakos darbai, 2022)
Usually, when associating humans and animals, they are discussed in general, i. e. presupposing the optimal status of both. Authentic texts by the Lithuanian poet Janina Degutytė (1928–1990) enter the intense interspecies discourse in a very particular way – by juxtaposing experiences of the animal, illness, age, pain, and the anticipation of death. Using the notion of becoming with the animal, introduced by Donna Haraway, the author of the article describes the identity of the ailing person, changing while the latter is with the cat. It could be said that the cat takes her out of the state of cowering inside and shutting herself in her illness. While being with the cat, the subject of the texts gradually accepts herself as an ill person, along with the lifeworld as it is. In the Western philosophy, pain and death are primarily perceived as a proof of the insurmountable solitude and individuality of a human being; allegedly, pain and death are not intersubjective. The cat described by Degutytė shares the human pain until death, allowing for reconsideration of the individual character of pain and death experience. Not unlike to the phenomenologist Alphonso Lingis, Degutytė reveals the human necessity to die in the company of another. In Degutytė’s case, this possibility is provided by the cat.